2011
DOI: 10.1017/s000711451100674x
|View full text |Cite
|
Sign up to set email alerts
|

Choline supplementation and measures of choline and betaine status: a randomised, controlled trial in postmenopausal women

Abstract: Choline is an essential nutrient and can also be obtained by de novo synthesis via an oestrogen responsive pathway. Choline can be oxidised to the methyl donor betaine, with short-term supplementation reported to lower plasma total homocysteine (tHcy); however, the effects of longer-term choline supplementation are less clear. We investigated the effect of choline supplementation on plasma concentrations of free choline, betaine and tHcy and B-vitamin status in postmenopausal women, a group more susceptible to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…Higher betaine concentrations were associated with a favorable risk-factor profile, and higher choline concentrations were associated with an unfavorable risk-factor profile (8). Plasma choline and betaine concentrations were comparable with those previously reported (8,(19)(20)(21)(22). Compared with the overall US population aged $65 y, the NAME population has a higher percentage of women, more college graduates, higher prevalences of diabetes and hypertension, and higher reported current alcohol consumption and cigarette use (23).…”
Section: Discussionsupporting
confidence: 78%
“…Higher betaine concentrations were associated with a favorable risk-factor profile, and higher choline concentrations were associated with an unfavorable risk-factor profile (8). Plasma choline and betaine concentrations were comparable with those previously reported (8,(19)(20)(21)(22). Compared with the overall US population aged $65 y, the NAME population has a higher percentage of women, more college graduates, higher prevalences of diabetes and hypertension, and higher reported current alcohol consumption and cigarette use (23).…”
Section: Discussionsupporting
confidence: 78%
“…The flow of methyl groups via the BHMT pathway is not dependent on folate or vitamin B12, but there are several cross-talk mechanisms between the BHMT and the folate pathways. Choline has been shown to indirectly support homocysteine methylation [15]. One study of postmenopausal women showed that choline supplementation increased plasma betaine levels and slightly lowered plasma levels of total homocysteine (tHcy) after six weeks (median change, −0.9 vs. +0.6 μmol/L in the placebo group: p = 0.058) and 12 weeks [15].…”
Section: Methyl Donors: Betaine and Cholinementioning
confidence: 99%
“…Choline has been shown to indirectly support homocysteine methylation [15]. One study of postmenopausal women showed that choline supplementation increased plasma betaine levels and slightly lowered plasma levels of total homocysteine (tHcy) after six weeks (median change, −0.9 vs. +0.6 μmol/L in the placebo group: p = 0.058) and 12 weeks [15]. Sex- and age-related differences in choline requirements and blood levels have been reported.…”
Section: Methyl Donors: Betaine and Cholinementioning
confidence: 99%
“…The findings from a 4-month RCT showed that women taking 20 lg HyD had significantly (À5.7 mmHg) lower blood pressure (P = 0.0002) (77) . In relation to choline supplementation, a 12-week trial recruiting 42 post-menopausal women found that 1 g of choline daily led to reduction in plasma homocysteine levels that approached statistical significance (P = 0.058) (86) . Finally, a 3-year follow-up study comprising 388 healthy adults showed that those with a history of coronary artery disease receiving 500 lg of phylloquinine daily had 6% less progression compared to those taking a standard multivitamin (P = 0.04) (74) .…”
Section: Metabolic Healthmentioning
confidence: 99%